HEPATOBILIARY SYSTEM IN PROMOTING OF WOMEN REPRODUCTIVE FUNCTION - Скрипник І. М.; Ліхачов В. К.; Добровольска Л. М.; Маслова Г. С. (World of Medicine and Biology, 2015)
In the article modern aspects of hepatobiliary system and its disorders in the physiological mechanisms that ensure women’s reproductive health. It is shown that the liver takes a leading part not only in protein, carbohydrate and lipid metabolism, and also affects the koahulyatsiy tion hemostasis, which has big importance in maintaining adequate circulation in the placenta-fetus system. Violation of the functional state of the liver can cause hormonal changes in women and, consequently, lead to the development of infertility and pregnancy is not a pathological pregnancy. In turn, pregnancy and its complications, such as early and late gestosis, contribute to stress on hepatocytes and in some cases damage to the development of cholestasis, hepatocellular failure, fatty liver.